(3TQM GdcGJj Ydi EjSGZhLjs - (3GdcGJj, MSGe GdOjf MSf, J (B760 (3g`s ((3eMeO Hf eUWai ScQjs)
(3ChdgG (B:s
(3GdMeO ddg hGLH hLhOg aEf cJGH GdTjN CKjQ GdOjf GdCHgQj GdeTghQ HEjSGZhLj deG cGf Ydi HYV GdENhGf eJYSQG hYdi HYVge eJjSQG CQOJ Cf GcJH HGdJeGSge ChQGbG dJRjd JYSQgs
(3BNQgG (B:s
(3Ch eDdaI ef ebOeGJ hgejI cGPHI Cj ZjQ hGbYI hgj bVjI jMce HgG hge GdGfSGf aj CehQ ZjQ eMShSI bjGSG Ydi GdCehQ GdeMShSI ceG jMce HCf cd ehLhO eJMjR dCfg jOQc Gf cd eG gh TGgO eMShS Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1/579s
(3cTa GdXfhf (B1\206s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs